Assessment of chlorophyll variability along the northwestern coast of Iberian Peninsula - Picado, A.
The northwestern coast of the Iberian Peninsula is characterized by a high primary production mainly supported by coastal upwelling, creating an extraordinary commercial interest for fisheries and aquaculture. Considering chlorophyll- a (Chl- a) as an indicator of primary production, its spatio-temporal variability was researched in this study in the surface water of this upwelling region from 1998 to 2007. Satellite derived Chl- a, Sea Surface Temperature (SST) and Ekman transport data as well as the inflow of the main rivers discharging into the study area were used to investigate the origin of the Chl- a concentration. Empirical Orthogonal Function (EOF) analysis of weekly Chl- a images was performed, as well as correlation analysis between Chl- a concentration, Ekman transport and river discharge. EOF results suggest that the highest Chl- a concentration occurs near the coast up to 60. km offshore. The interannual variability of Chl- a, SST and Ekman transport was also studied considering summer and winter months. Generally, 2005, 2006 and 2007 were the most productive years during the summer months with high Chl- a concentrations along the coast associated to the strong upwelling conditions observed. Otherwise, 1998 seemed to be the most productive year during winter. The absence of upwelling favorable conditions together with localized low SST and considerable discharges, suggests that the high Chl- a concentrations observed during this period are mainly due to the entrance of nutrients through river runoff. However, in winter, high concentrations of colored dissolved organic matter (CDOM), associated with river runoff, are present in the ocean surface, leading to an erroneous strong signal of the satellite. During winter correlations of 0.58 and 0.49 were found between Chl- a concentration and Douro and Minho discharges, respectively, evidencing that high Chl- a concentration was related with river runoff. Otherwise, during summer, Chl- a and Ekman transport exhibited a correlation of - 0.38 indicating that high Chl- a is associated to upwelling events. In summary, it was found that the spatio-temporal variability of Chl- a along the northwestern coast of Iberian Peninsula exhibited the clear influence of upwelling events during summer. Conversely, the variability during winter was mainly due to entrance of nutrients through the rivers discharge which flow into the area.